Modeling carrier density dependent charge transport in semiconducting carbon nanotube networks - Schießl, Stefan Patrick; Rother, Marcel; Brohmann, Maximilian; Zaumseil, Jana (Physical review materials, 2017)
Charge transport in a network of only semiconducting single-walled carbon nanotubes is modeled as a random-resistor network of tube-tube junctions. Solving Kirchhoff's current law with a numerical solver and taking into account the one-dimensional density of states of the nanotubes enables the evaluation of carrier density dependent charge transport properties such as network mobility, local power dissipation, and current distribution. The model allows us to simulate and investigate mixed networks that contain semiconducting nanotubes with different diameters, and thus different band gaps and conduction band edge energies. The obtained results are in good agreement with available experimental data.
Gesehen am 04.05.2018